C-reactive protein associated with periodontitis in a Thai population - Grit Meissner (Blackwell Synergy, 2008)
Aim: We have recently tested a surface detection system based on a conventional dental ultrasonic scaler in vitro. The aim of the present study was to investigate sensitivity and the specificity of the detection device in vivo. Material and Methods: Subgingival buccal surfaces of 63 arbitrarily selected periodontally compromised teeth were scanned intra-orally, while the supragingival positions of the insert, along with the corresponding signals of the detection system, were saved as separate files. After extraction, the surface detection results were evaluated by re-positioning the inserts’ position on the tooth in vitro and comparing the detection results with visual findings. Results: On the scanned tooth surfaces, there were 44 calculus spots, which covered 22.3% of all scanned surfaces (prevalence). The calculus-free surface was divided into ‘‘spots’’ mathematically. The device correctly classified 40 calculus and 125 cementum spots, whereas four calculus and 28 cementum spots were classified incorrectly. Calculus and cementum were discriminated with a sensitivity of 91% and a specificity of 82%. The positive and negative predictive values were 0.59 and 0.97. Conclusion: The surface detection device was able to clinically differentiate cementum and calculus in vivo. Therefore, this method may support the decision of whether continued subgingival scaling could damage the cementum.